Transitivity of the surface measures on Banach manifolds with uniform structure - Bogdanskii, Yu. V.; Moravets’ka, E. V. (Ukrains’kyi Matematychnyi Zhurnal, 2017)
We perform the analysis of transitivity of associated measures on the surfaces with finite codimension imbedded in a Banach manifold with uniform atlas.